Advancing patient safety in interventional radiology: effective dose evaluation and LDRL - Alvarez, M. [UNESP] (2025)
This study highlights the significance of radioprotection in interventional radiology, focusing on the assessment of Effective Dose values to which patients are exposed. To facilitate this, we developed a semi-automatic software employing Optical Character Recognition technology. This software analysed 1334 interventional procedures conducted between January 2021 and September 2023 at a large Brazilian hospital. The database includes the type of procedure, Air Kerma value, Kerma-Area Product, number of cineangiography images, and exposure duration, all realized on an Artis Zee® (Siemens Healthineers, Germany) C-arm. We established Local Diagnostic Reference Levels (LDRLs) and calculated Effective Dose values using the PCXMC 2.0 Monte Carlo simulation software. These calculations were based on data from the hospital and LDRLs determined in subsequent studies. The findings reveal that both the LDRLs and the calculated Effective Dose generally fall below the values reported in existing literature. This underscores the efficacy of our methodology in enhancing radioprotection and dose monitoring within the studied hemodynamics sector.